Social Change Philanthropy: The Role Of Rumah Zakat In Mobilizing Muslim Civil Society Against Poverty - Hannani, Hannani; Nurkidam, Nurkidam; Mahyuddin, Mahyuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
Currently, the problem of poverty is one of the social problems in Indonesia. Therefore, it needs a strategy to solve it. The purpose of this paper is to present an approach of Rumah Zakat aimed at mobilizing civil society in reducing the poverty gap. This study used the descriptive method and qualitative analysis. The data source was secondary data collected from documents and texts related to the topic, be it books, articles, newspapers, and journals. This study found the that socio-economic empowerment of Rumah Zakat had a role in providing social change in the communities where the contribution of the program’s productive implementation has an impact in reducing the depth severity of poverty in Indonesia. The provision of voluntary charity through empowering programs in Muslim civil society is needed to bring welfare to the communities